Evaluation of the efficacy and safety of three dosing regimens of agalsidase alfa enzyme replacement therapy was underpowered - Ortiz A; Sanchez-Niño MD (Dove Medical Press, 2015)
Alberto Ortiz,1,2 Maria Dolores Sanchez-Niño1,2 1Department of Nephrology, IIS-Fundacion Jimenez Diaz, School of Medicine, Universidad Autónoma de Madrid, 2Department of Nephrology, Instituto Reina Sofia de Investigación Nefrológica, Madrid, Spain We read with interest the report by Goláň et al on the “Evaluation of the efficacy and safety of three dosing regimens of agalsidase alfa enzyme replacement therapy in adults with Fabry disease”.1 Based on the reported results, the authors conclude that no efficacy or safety differences were found when the approved every-other-week (EOW) dosage of agalsidase alfa was increased to weekly administration. However, the key question is whether the study, as designed and performed, could have had a different outcome. View original article by Goláň et al.